Short Communication: Update phylogenetic information of the local varieties of cloves (Syzygium aromaticum) from North Maluku, Indonesia based on ITS sequences data - SUNDARI SUNDARI; NURHASANAH NURHASANAH; ABDU MAS’UD; MOHAMAD AMIN; ESTRI LARAS ARUMINGTYAS; RODIYATI AZRIANINGSIH (Society for Indonesian Biodiversity, 2019)
Abstract. Sundari, Nurhasanah, Mas'ud A, Amin M, Arumingtyas EL, Azrianingsih R. 2019. Update phylogenetic information of the local varieties of cloves (Syzygium aromaticum) from North Maluku, Indonesia based on ITS sequences data. Biodiversitas 20: 1510-1515. Clove (Syzygium aromaticum L. Merr & Perry) is a native spice plant species in Indonesia, especially Maluku and North Maluku. The phylogenetic relationship among local varieties of cloves in North Maluku, Indonesia is currently unclear; therefore molecular verification research is required for further conservation and breeding programs. This study aims to identify the taxonomic position and phylogenetic relationship among two valuable local varieties of cloves rom North Maluku, i.e., ’Afo’ and ’Sibela’, based on ITS sequences data. Afo clove is considered as the oldest clove native to Ternate island, and Sibela clove is the oldest clove native to Bacan Island. The phylogenetic analysis using both Maximum Parsimony and Neighbour Joining algorithms confirmed the monophyletic group of cloves (S. aromaticum) and separated to outgroup of Eugenia species. Both phylogenetic trees produced three clades with the same pattern and supported by strong bootstrap values of 99-100%.